Halina Ho Photograph of 85C - Ho, Halina::::::::: (2021)
Photograph taken by Halina Ho took a photograph outside of 85C bakery. The contributor writes, "It was May 5, 2020 and my mother's birthday. I have not physically gone out for so long and decided to surprise her with a cake from her favorite bakery 85'c."